Resistência à fadiga e comportamento em torção de instrumentos endodônticos de NiTi Profile - Maria Guiomar de Azevedo Bahia (2004)
A comparative study of the torsion behavior and of the fatigue resistance of rotary NiTi endodontic instruments was performed in this work. ProFile 20/.04, 25/.04, 30/.04, 20/.06, 25/.06 e 30/.06 instruments were analyzed at the following conditions: Control Group 01, containing 10 non-used instruments of each size and taper, tested until rupture in fatigue in a bench machine, inside an artificial canal made of quenched toolsteel, with a 5mm curvature radius and an angle of curvature of 45°; Experimental Group 01, with 15 instruments of each type, previously employed for cleaning and shaping the root canal system of 10 curved canals in human molars during normal clinical practice; Control Group 02, with 10 non-used instruments of each size and tape, tested until breakage in torsion, according to Specification No. 28 of the American Dental Association ADA; Experimental Groups 02 and 03, each group containing 10 instruments of the same size and taper, previously submitted to fatigue tests interrupted at 1/2 and 3/4 of the instruments fatigue life. Analysis of the results obtained showed that the fatigue resistance of Profile instruments, measured by the number of cycles to failure, varies inversely with the strain amplitude. Besides that, the use of the instruments for cleaning and shaping 10 curved radicular canals reduces in more than 50% their fatigue life. It has also been observed that the instruments fatigued up to 1/2 and 3/4 of their fatigue life decrease their resistance in torsion by 29 and 32%, respectively. Analysis of the fracture surfaces showed that the presence of multiple secondary cracks, whose nucleation is probably associated to the high density of interfaces and other structural imperfections in martensite, may give rise to an efficient mechanism for the dissipation of energy, being, thus, the main mechanism responsible for the slow fatigue crack propagation in NiTi alloys.